Effect of Moringa Oleifera leaves powder on hemoglobin level in second-trimester pregnant women of Karachi, Pakistan. - Ashfaq, Sana; Sajid, Ujala; Khan, Saima; Saleem, Yusra; Batool, S. Farah; Zafar, Shaheen; Akber, Syeda Sadaf; Sultan, Syed Akmal (International Journal of Endorsing Health Science Research, 2024)
Background: Anemia, particularly iron-deficiency anemia during pregnancy, has substantial implications for maternal health and fetal growth. Moringa leaves are known to be rich in iron and may offer a dietary solution to combat anemia in pregnant women. However, evidence on the association between fresh Moringa leaf consumption and maternal hemoglobin levels during pregnancy is lacking. Hence, this study aims to assess the impact of Moringa Oleifera leaf powder supplementation on hemoglobin levels during the second trimester of pregnancy in Karachi, Pakistan. Methodology: A community-based comparative cross-sectional study was conducted at Koohi Goth Women's Hospital, Karachi, Pakistan, from November 2021 to May 2023. The study involved 200 pregnant women who consumed fresh Moringa leaves and 200 non-consumers. Data were collected through an interviewer-administered structured questionnaire, and hemoglobin levels were measured using HemoCue Hb 301. Results: The demographic characteristics of the study participants were analyzed, revealing that most participants in both groups were between 20 and 30 years old. Additionally, most participants in both groups were pregnant for the first time. Hemoglobin (Hb) levels were measured across trimesters, with the Moringa leaf extract group showing levels of 9.43 ± 0.62 g/dL in the first trimester, 8.98 ± 1.12 g/dL in the second trimester, and 9.09 ± 1.04 g/dL in the third trimester. The folic iron group exhibited a higher increase in hemoglobin concentration (10.14 ± 0.91 g/dL) compared to the Moringa leaf extract group (8.98 ± 1.12 g/dL), but the difference between the two groups was not statistically significant. Conclusion: In conclusion, iron-rich foods such as Moringa leaves and iron tablets are recommended to enhance hemoglobin levels in pregnant women.